2008
DOI: 10.1080/07853890701771823
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: A new class of gene regulators

Abstract: Elucidation of the molecular basis of disease depends upon continued progress in defining the mechanisms by which genomic information is encoded and expressed. Transcription factor-mediated regulation of mRNA is clearly a major source of regulatory control and has been well studied. The more recent discovery of small RNAs as key regulators of gene function has introduced a new level and mechanism of regulation. Mammalian genomes contain hundreds of microRNAs (miRNAs) that each can potentially downregulate many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
133
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(134 citation statements)
references
References 156 publications
0
133
0
1
Order By: Relevance
“…MicroRNA expression has been examined in various tumors (Guarnieri and DiLeone, 2008;Lu et al, 2005;Nicoloso and Calin, 2008), in Alzheimer's disease (Hebert et al, 2008), Parkinson's disease (Kim et al, 2007), Down's syndrome (Kuhn et al, 2008), schizophrenia (Beveridge et al, 2008), and stroke (Dharap et al, 2009;Jeyaseelan et al, 2008). These miRNA expression profiles may be as diagnostically useful as mRNA expression profiles (Guarnieri and DiLeone, 2008;Lu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNA expression has been examined in various tumors (Guarnieri and DiLeone, 2008;Lu et al, 2005;Nicoloso and Calin, 2008), in Alzheimer's disease (Hebert et al, 2008), Parkinson's disease (Kim et al, 2007), Down's syndrome (Kuhn et al, 2008), schizophrenia (Beveridge et al, 2008), and stroke (Dharap et al, 2009;Jeyaseelan et al, 2008). These miRNA expression profiles may be as diagnostically useful as mRNA expression profiles (Guarnieri and DiLeone, 2008;Lu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are only hundreds of miRNAs, each of them can potentially regulate hundreds of target genes (Guarnieri and DiLeone, 2008), with the prediction that more than one-third of all human genes may be regulated by miRNAs (EsquelaKerscher and Slack, 2006). Functionally, miRNAs are implicated in fundamental cellular processes including cell-cycle regulation (Matsubara et al, 2007), hematopoietic differentiation (Hatfield and RuoholaBaker, 2008), immune responses (Bi et al, 2009), and cellular metabolism (Gauthier and Wollheim, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous molecules that post-transcriptionally regulate target gene expression [4][5][6]. In many cases, the identification of specific targets of miRNAs has highlighted important cellular events and demonstrated that aberrant microRNA expression is a common feature of many diseases [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that miRNAs exhibit a variety of crucial regulatory functions related to many fundamental aspects of life (2)(3)(4)(5). In recent years, deregulated expression of miRNA has also been found to be associated with various human diseases (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%